PERENCANAAN PENGELOLAAN SAMPAH DI KELURAHAN MUARA JAWA ULU DAN MUARA JAWA PESISIR KABUPATEN KUTAI KARTANEGARA - Edhi Sarwono; Yudhistiro Indro Saputro; Budi Nining Widarti (Mulawarman University Press, 2017)
AbstractDuring this timemost peoplestillconsider waste asthe restuseless. In an effort to raise the awareness in handling environmental issues, particularly waste and to create a quality residential clean and friendly environment tthen it must be a paradigm shift waste management by reducing the volume of waste from the source. In this study,the first stage is to identify the problem of garbage contained in the study area, the second secondary data and primary data. And the last one is to determine the right way to waste management in the study area. The final results of this study concluded that waste generation in the village of Muara Jawa and Muara Java UluCoastal namely high levels of economic heft 245,625 kg and the volume of waste 185,8 liters, the economy is having severe level waste 291,95 and the volume of garbage 179,7 liters, having a low economic level waste weight 432,925 and the volume of garbage 158,5 liters. And in the village of Muara Jawa Ulu and Muara Jawa Pesisir be created with an area of 600meter2 dump site. Key words: trash, source waste, integrated waste managament location